EVOLUTION OF DIPLOMACY AND THE FUTURE OF EPISTEMIC COMMUNITIES: SCIENTISTS AS THE DIPLOMATS OF THE 21ST CENTURY - Sutcu, Guliz (European Scientific Journal, ESJ, 2012)
The structure of world politics has changed to a great extent due to the increasing variety and number of actors and issues that matter for the conduct of international relations. This led to a change in the way that diplomatic communication operates between states. With the diversification of means and interlocutors of diplomacy, diplomacy has evolved and science has been recently understood as a diplomatic tool. Due to this, epistemic communities have appeared as the new actors of diplomacy. As the importance of epistemic community for establishing international relations based on trust has increased, states have started to conduct science diplomacy and to appoint ‘science envoys’ to foreign countries in order to get maximum benefit from the science diplomacy activities.